Contesting masculinities: a study of selected texts of resistance to conscription into the South African Defence Force (SADF) in the 1980s - Mason, Paul (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2016)
The theoretical framework for this thesis and analysis of primary texts revolves around the problem of conscription into the South African Defence Force (SADF) in the 1980s. The ideology of masculinity that underpinned and sustained the practice of conscription is referred to throughout as the hegemonic version. This term is interchangeable with others, namely masculinism and "—the real man.' The aim is to interpret the selected texts for strains of resistance to the practice of conscription and its assumptions as to what to what constitutes the natural or real man. In the Introduction to this thesis I begin by explaining the personal dimension of my role as researcher, after which I motivate my research project and explain its theoretical and methodological orientation, focusing on the concepts that play a significant role in analysis of the primary texts. The Introduction concludes with an outline of the content of Chapters 1"“5. Chapter 1 begins with a brief discussion, on the general level, of the practice of conscription and resistance to it, and proceeds to a concern with conscription in 1980s South Africa. Attention is paid to prevailing attitudes towards gender and sexuality within both the SADF and the End Conscription Campaign (ECC). Discussion of gender and sexuality as constructs of identity proceeds to a focus on the conceptual tools for textual analysis provided by theories of masculinity. The final section of this chapter pays attention to specific post-structuralist notions of identity that serve analysis of the primary texts, that is, the notions of the subject, agency and the author. Having engaged mainly with secondary texts in Chapter 1, Chapter 2 presents the first sustained critical engagement with primary texts in which resistance was expressed against the institution of conscription and the hegemonic version of masculinity that underpinned it. These expressions of resistance occurred within a rock music counter-culture of the period, known as the Voëlvry movement. Attention is given to overlaps or links between this counter-culture and that of America in the 1960s, as well echoes between the Vietnam and Border Wars. Analysis of these links is applied to a memoir selected for its appropriateness. Threaded through the chapter is a concern with expressions of masculine identity within the Voëlvry counter-culture, the SADF and the ECC. Chapter 3 focuses on three novels and one collection of short stories, each narrated in the first person and written by gay authors who performed their National Service. Attention is paid to the protagonists' perceptions of themselves, their troubled relationships with their fathers, and the struggle to come out within a context that prohibited them from doing so. Chapter 4 concerns three wartime memoirs and two written by men who refused to perform their National Service. Underlying concerns in this chapter are the question of fact versus fiction in the genre of the memoir, authors' perceptions of and relationships with women, and expressions of vulnerability. Chapter 5 concentrates on the interviews that comprise the Appendix. The chapter establishes its theoretical ground by focusing on principles of narrative structure and the relation of personal to narrative identity. The chapter pays attention to the displays of power and the vulnerabilities of both veteran soldiers and resisters. Theory deployed in analysis of the primary texts serves the principal concerns articulated in the title to the thesis.
Keywords: Uncatalogued